Insights into early stage of antibiotic development in small- and medium-sized enterprises: a survey of targets, costs, and durations - Christine Årdal; Enrico Baraldi; Ursula Theuretzbacher; Kevin Outterson; Jens Plahte; Francesco Ciabuschi; John-Arne Røttingen (Taylor & Francis Group, 2018)
Background Antibiotic innovation has dwindled to dangerously low levels in the past 30 years. Since resistance continues to evolve, this innovation deficit can have perilous consequences on patients. A number of new incentives have been suggested to stimulate greater antibacterial drug innovation. To design effective solutions, a greater understanding is needed of actual antibiotic discovery and development costs and timelines. Small and medium-sized enterprises (SMEs) undertake most discovery and early phase development for antibiotics and other drugs. This paper attempts to gather a better understanding of SMEs' targets, costs, and durations related to discovery and early phase development of antibacterial therapies. Methods DRIVE-AB, a project focused on developing new economic incentives to stimulate antibacterial innovation, held a European stakeholder meeting in February 2015. All SMEs invited to this meeting (n = 44) were subsequently sent a survey to gather more data regarding their areas of activity, completed and expected development costs and timelines, and business models. Results Twenty-five companies responded to the survey. Respondents were primarily small companies each focusing on developing 1 to 3 new antibiotics, focused on pathogens of public health importance. Most have not yet completed any clinical trials. They have reported ranges of discovery and development out-of-pocket costs that appear to be less expensive than other studies of general pharmaceutical research and development (R&D) costs. The duration ranges reported for completing each phase of R&D are highly variable when compared to previously published general pharmaceutical innovation average durations. However, our sample population is small and may not be fully representative of all relevant antibiotic SMEs. Conclusions The data collected by this study provide important insights and estimates about R&D in European SMEs focusing on antibiotics, which can be combined with other data to design incentives to stimulate antibacterial innovation. The variation implies that costs and durations are difficult to generalize due to the unique characteristics of each antibiotic project and depend on individual business strategies and circumstances.